Aktivitas Minyak Ikan dalam Menghambat Preneoplasia Kolon Mencit yang Diinduksi Azoksimetan dan Dextran Sodium Sulfate - KUSMARDI KUSMARDI; BAMBANG PONTJO PRIOSOERYANTO; EVA HARLINA; SANTOSO CORNAIN (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Epidemiologic studies of dietary marine n-3 fatty acids and risk of colorectal cancer have been inconsistent. The study was conducted to understand the inhibitory effect of fish oil in mice with colorectal preneoplasia induced by azoxymethane (AOM) and dextran sodium sulfate (DSS). In this study, Balb/c mice was induced by AOM 10 mg/kg body weight followed by administration of 1 % DSS during a week. Fish oil administrated orally at a dose of 1.5, 3, and 6 mg per day. Histopathological examination of the colon tissue (hematoxylin-eosin staining) was done by counting the number of inflammation, and hyperplasia foci, the number of mitosis epithelial cells, and the scores of dysplasia in ten visual fields. In the second month, decreasing in the number of inflammation foci occurred between the control and low dose groups with medium and high dose groups (p<0,05). While in the third and fourth month, decreasing in the number of inflammation foci were observed in all treatment group (p<0.001). The number of mitotic colonic crypt epithelial cells was statistically significant between control group and treatment groups, initially observed since the second month. In the second month to the fourth month, generally increasing of doses of fish oil has decreased the number of hyperplasia foci. Our research indicates that fish oil also inhibits the occurrence of dysplasia. In the third and fourth month, dysplasia was found in the control group. Dysplasia was found only in the fouth month in the treatment group.